Peningkatan Pertumbuhan dan Hasil Jagung Manis dengan Pemanfaatan Trichokompos dan POC Daun Lamtoro - Mukhofifatul Ainiya; Moch Fadil; Rika Despita (Agrotechnology Research Journal, 2019)
Fertilization is an effort to increase the production of sweet corn corp. The tendency of excessive use of inorganic fertilizers can lead to decreased land productivity. One attempt to improve soil fertility is the organic matter that can improve the physical, chemical and biological soil. The objective of this research was to study the benefit of Trichokompos and liquid organic fertilizer lamtoro leaves to increase growth and yield of sweet corn. The research conducted in Keling Village, Kepung Subdistrict, Kediri Regency from December 2018 - March 2019. The method used was Factorial Randomized Completed Block Design (RCBD) with two factors and 3 replications. The first factor, Trichokompos consists of 3 levels of experiment (0 ton/ha, 20 ton/ha, 25 ton/ha). The second factor, liquid organic fertilizer of Leucaena leucocephala (Lam.) consists of 3 levels of experiment (0 ml plant-1, 200 ml plant-1, 250 ml plant-1). The results showed that the treatment of Trichokompos 25-ton ha-1 and liquid organic fertilizer of Leucaena leucocephala (Lam.) 250 ml plant-1 could increase the growth and yield of sweet corn plants compared to other treatments.